ANALISIS DEBIT BANJIR RANCANGAN UNTUK NORMALISASI SALURAN DRAINASE DAN DESAIN DINDING PENAHAN TANAH DI DAERAH SEKITAR SUNGAI EPHEMERAL - ANAK AGUNG RATU RITAKA WANGSA; PUTU MIA DEVI PADILLA (GANEC SWARA, 2023)
Rehabilitation of buildings around the area around the river is considered by the owner of the activity because during high rainfall it will cause flooding. Flooding will result in delays in the building rehabilitation process because river water overflows into the activity location. One of the areas around a river in Bali, namely Tukad Bangin located in Pecatu Badung, is an ephemeral river, namely a river whose water only exists during the rainy season and often floods due to abnormal drainage channels and the absence of retaining walls. In the environment around Tukad Bangin there are buildings which during the rainy season cause frequent flooding, so a plan for building rehabilitation is carried out by making drainage channels and senders, then the results of calculating the design flood discharge in the Tukad Bangin Pecatu Badung area are carried out. The method used in this study is a quantitative method, namely measuring from direct observation at Tukad Bangin and then calculating the design flood discharge for various return periods for planning the design of drainage channels and shores. The results of the design flood discharge analysis with Q1 year are 15.47 m3/sec, Q2 year is 49.74 m3/sec and Q5 year is 65.89 m3/sec. From the simulation results of the water surface profile, the extreme depth values for discharge at 2-year return period are 1.54 m, 5-year return periods are 1.80 m, 10-year return periods are 1.93 m, 25-year return periods are 2.06 m and a 50-year return period of 2.04 m, so that with the HEC-RAS modeling it can control the height of the flood protection embankment and the design of the planned drainage channels and canals can be carried out.